2017
DOI: 10.1371/journal.pone.0181199
|View full text |Cite
|
Sign up to set email alerts
|

Gallic acid/hydroxypropyl-β-cyclodextrin complex: Improving solubility for application on in vitro/ in vivo Candida albicans biofilms

Abstract: The aim of this study was to increase the solubility of gallic acid (GA) for the treatment of Candida albicans biofilm, which is very difficult to treat and requires high drug concentrations. Cyclodextrins (CDs) were used for this purpose. Complexes were evaluated by phase-solubility studies, prepared by spray drying and characterized by drug loading, scanning electron microscopy (SEM) and differential scanning calorimetry (DSC). The complexes were tested on C. albicans biofilm using in vitro and in vivo model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
3
20
0
Order By: Relevance
“…This points out to a promising antifungal activity of AF. For comparative purposes, all the data corresponding to GA 2X MIC and AmB (2 μg ml -1 ) were extracted from another study performed by our group ( Teodoro et al, 2017 ). It is important to highlight that all these experiments were performed simultaneously.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This points out to a promising antifungal activity of AF. For comparative purposes, all the data corresponding to GA 2X MIC and AmB (2 μg ml -1 ) were extracted from another study performed by our group ( Teodoro et al, 2017 ). It is important to highlight that all these experiments were performed simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…∗ P < 0.05, ∗∗∗ P < 0.0001; ns, not statistically significant. Ψ: Data collected from Teodoro et al (2017) . Tests were performed in triplicate in three independent experiments using C. albicans ATCC 18804, SC5314 and three clinical strains ( n = 45 for each group).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, methods have been developed for the enhancement of bioavailability or biologically relevant application of GA. For example, to improve GA solubility for treating C. albicans biofilms, antifungal efficacy of GA/hydroxypropyl-β-cyclodextrin complex (HPβCD) has been examined (Teodoro et al, 2017). Results showed that GA/HPβCD complex was active against C. albicans biofilms, where the complex preserved the antifungal potency of the pure GA while it also exerted anti-inflammatory activity.…”
Section: Introduction (Continued)mentioning
confidence: 99%